Prediction of residual pipeline resource taking into account the operation loading conditions - Banahevych, Yu.V.; Andreykiv, O.E.; Kit, M.B. (Проблемы прочности, 2009)
An effective energy approach to the evaluation of the residual service life of a pipe of oil pipeline containing a crack on its inner surface for the two-frequency loading mode of biaxial tensioncompression has been proposed. The two-frequency variations of pressure in the pipe are caused by the turbulence of the flow of oil (highfrequency), opening and closing of the gate valves, and the shutdowns of the pumps (low frequency). Предложен эффективный энергетический подход к оценке остаточного эксплуатационного ресурса нефтепровода с трещиной на внутренней поверхности трубы, подвергаемой двухчастотному биаксиальному нагружению растяжением-сжатием. Двухчастотный режим изменения давления в трубопроводе обусловлен турбулентностью потока нефти (высокочастотная составляющая), открыванием и закрыванием задвижек, а так же отключением нефтенасосов (низкочастотная составляющая).